Teamwork Perceived by the Staff, Environment and Sanitation Section.District Office in Bangkok, Bangkok Metropolitan Administration* - Kaewcumrod, Piyanuch (วารสารพยาบาลเกื้อการุณย์, 2015)
The objective of this explanatory research was to analyze the relation among personal characteristics, the number of team member, communication and working atmosphere with team work as perceived by the officers of environment and sanitation section, Office of the District, Bangkok Metropolitan. The data was collected from the officers of the Office of the District, Bangkok Metropolis Municipality who were working in the Environment and Sanitation Section of Bangkok Metropolis. The samples were selected by Purposive sampling from sanitation officers at the operational level, along with specialized experts and public health officers from operational level to expert level. There were 218 samples and 175 returned questionnaires. The data were collected by using questionnaires during the period from 15th May – 15th June 2013. The data were analyzed by using computerized packaged program; statistics used were percentage, mean, standard deviation and Pearson’s Product Correlation Coefficient. The study found that the majority of the populations were female; age 21-30 years old; bachelor degree; holding the position as a sanitary technical officer at an operational level; working experience 1-5 years, and the average team consisted of 2-4 team members. The communication, working atmosphere, and team work as perceived by the studied population were at a high level (= 4.05, 3.80 and 3.78 consecutively). The study found no association between personal characteristics and number of person in a team with team work as perceived by the studied population. The study found the association between communication and working atmosphere with team work as perceived by the studied population in medium level and high level with statistical significance at p-value<0.001 (r = 0.692 and 0.801 consecutively). This researcher suggests there should be development of team work in the Environment and Sanitation Section in Office of the District, Bangkok Metropolitan in the aspect of the component of team by allocating the working role in accord with the capability, personality and the interest of the member. Each member should accept the state of working with other person and promote the working atmosphere. Team leader should take action in resolving conflict, creating common consciousness of responsibility so that cooperation and positive attitude be mutually created through having activity and working together.